Laser-Induced Graphene as Electrode Material in Proton-Exchange Membrane Fuel Cells - Tommaso Serra; Giulia Massaglia; Pietro Zaccagnini; Marco Fontana; Candido Fabrizio Pirri; Giancarlo Cicero; Stefano Bianco; Marzia Quaglio (Materials Proceedings, 2023)
The preparation of graphene foams via laser pyrolysis of polyimides has gained success due to its ease and speed of processing. Established applications of laser-induced graphene (LIG) involve micro-supercapacitors, batteries, sensors, and water treatment. However, to the best of our knowledge, only a few studies have focused on potential applications of LIG in proton-exchange membrane fuel cells (PEM-FCs). In this study, we demonstrate that LIG obtained from SPEEK films (LIG-S) presents all the key features required of a PEM-FC electrode. Moreover, electrochemical tests in rotating disk and half-cell setups highlight the intrinsic catalytic activity of LIG towards the oxygen reduction reaction. This activity is attributed to structural defects in the LIG lattice and sulfur doping incorporated from the SPEEK precursor, and it may lower the catalyst loading required to reach competitive cell performance.